The Antagonism of Corticotropin-Releasing Factor Receptor-1 in Brain Suppress Stress-Induced Propofol Self-Administration in Rats - Dong, Zhanglei; Zhang, Gaolong; Xiang, Saiqiong; Jiang, Chenchen; Chen, Zhichuan; Li, Yan; Huang, Bingwu; Zhou, Wenhua; Lian, Qingquan; Wu, Binbin (Frontiers in Behavioral Neuroscience, 2021)
Propofol addiction has been detected in human and rats, which may be facilitated by stress. Corticotropin-releasing factor (CRF) acts through CRF receptor-1 (CRF1R) and CRF2R, and is a crucial candidate target for the interaction between stress and drug abuse, but the role on propofol addiction remains unknown. Tail clip stressful stimulation was performed in rats to test the stress on the establishment of propofol self-administration behavioral model. Thereafter, the rats was pretreated before the testing session at bilateral lateral ventricle with one of the doses of antalarmin (CRF1R antagonist, 100-500 ng/site), antisauvagine 30 (CRF2R antagonist, 100-500 ng/site) and RU486 (glucocorticoid receptor antagonist, 100-500 ng/site) or vehicle. The dopamine D1 receptor (D1R) in the nucleus accumbens (NAc) was detected to explore the underlying molecular mechanism. The sucrose self-administration establishment and maintenance, and locomotor activities were also examined to determine the specificity. We found that the establishment of propofol self-administration was promoted in the tail clip treated group (the stress group), which was inhibited by antalarmin at the dose of 100-500 ng/site but was not by antisauvagine 30 or RU486. Accordingly, the expression of D1R in the NAc was attenuated by antalarmin dose dependently. Moreover, pretreatments fail to change sucrose self-administration behavior or locomotor activities. This study supports a role of CRF1R in brain in mediating the central reward processing through D1R in the NAc and provided a possibility that CRF1R antagonist may be a new therapeutic approach for the treatment of propofol addiction.